Measuring Content Validity: Students’ Self-efficacy and Meaningful Learning in Massive Open Online Course (MOOC) Scale - Ghazali, Norliza; Nordin, Mohamad Sahari; Hashim, Sulaiman; Hussien, Suhailah (2018)
The objective of this research is to examine the content validity of students’ self-efficacy and meaningful learning scale in context of Massive Open Online Course (MOOC) by using Content Validity Ratio (CVR). The research was conducted through the evaluation among 20 expert panels with purposive sampling technique. Expert panels were divided into two categories which are professional experts and field experts. Nine professional university experts involved with the respective expertise in psychology, psychometric, educational measurement and MOOC. The field experts consisted of eleven doctor of philosophy (PhD) candidates who is studying in public university in Malaysia and specializing in particular fields of study. The scale contains of two aspects which is students’ self-efficacy and meaningful learning. Students’ selfefficacy is conceptualized in four constructs with 35 items. Meanwhile for meaningful learning, there have five construct with 50 items. The results of the research show that the scale has a good content validity and proved that the scale has great potential to be promoted as a good scale of students’ self-efficacy and meaningful learning in context of MOOC. It is suggested to apply more sophisticated statistical analysis, such as the Structural Equation Modelling for elaborating on quality items and model development.